Prospective observational study of inside-out versus outside-in transobturator tapes for female stress urinary incontinence at a tertiary care hospital of South Western railway - Kanakaraya, Jamuna; Kanakaraya, S.; Kanakaraya, Naveen; Kanakaraya, Naren (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To compare outcomes of transobturator tension-free vaginal tape using outside-in and inside-out approaches in women with stress urinary incontinence (SUI), and to identify risk factors for treatment failure. Methods: A prospective observational study was conducted at Central Hospital, Hubli, from July 2007 to June 2022. A total of 223 women with SUI refractory to conservative management were enrolled; 129 underwent the inside-out (TVT-O) procedure and 94 underwent the outside-in (TOT) procedure. Patients were followed annually for at least 3 years (maximum 10 years). Subjective and objective cure rates, complications, quality of life (QoL), and psychological outcomes were assessed. Results: At 5 years, subjective cure rates were 87% for TVT-O and 83% for TOT, while objective cure rates were 95.3% and 90%, respectively. Both techniques demonstrated significant improvements in QoL and Beck depression inventory scores. Dyspareunia was higher in the TVT-O group (p=0.02), but other complication rates were comparable. In 75 patients with 10-year follow-up, long-term success was maintained at 97%. Conclusions: Both TVT-O and TOT techniques are safe and effective for treating female SUI, with durable long-term results. The choice of procedure should be guided by surgeon expertise and patient preference.